Learning reactive programming with Java 8 : learn how to use RxJava and its reactive observables to build fast, concurrent, and powerful applications through detailed examples /: learn how to use RxJava and its reactive observables to build fast, concurrent, and powerful applications through detailed examples. (2015) - Tsvetinov, Nickolay
No abstract available